The efficacy and toxicity of irinotecan with leucovorin and bolus and continuous infusional 5-fluorouracil (FOLFIRI) as salvage therapy for patients with advanced gastric cancer previously treated with platinum and taxane-based chemotherapy regimens - (:unkn) unknown (MANEY PUBLISHING, 2012)
There is no established standard salvage chemotherapy in the second-line setting for patients with advanced gastric cancer (AGC) pre-treated with platinum and taxane-based chemotherapy. Our study aims to evaluate the safety and efficacy of FOLFIRI regimen (irinotecan with leucovorin and bolus and continuous infusion with 5-fluorouracil) as a salvage chemotherapy regimen in patients with AGC. Medical records of 97 patients with AGC who received second-line FOLFIRI regimen between March 2006 and February 2011 were examined. Complete and partial responses were observed in 3 (3.1%) and 23 (23.7%) patients, respectively. The median time to progression (TTP) was 3.5 months (95% CI: 2.4-4.6) and the median overall survival (OS) was 10.5 months (95% CI: 8.8-12.2). The most common observed grade 3/4 toxicities were neutropenia (23.7%), diarrhea (6.2%), and stomatitis (5.2%). FOLFIRI regimen is safe and effective in the second-line treatment of AGC patients pre-treated with cisplatin and taxanes.
Keywords: Advanced gastric cancer; Salvage therapy; FOLFIRI regimen; HIGH-DOSE LEUCOVORIN; PHASE-III TRIAL; 1ST-LINE THERAPY; SUPPORTIVE CARE; PLUS CISPLATIN; FLUOROURACIL; FLUOROPYRIMIDINE; COMBINATION; ESOPHAGEAL; CARCINOMA